Pertanggungjawaban Hukum terhadap Anak yang Melakukan Tindak Pidana Pembunuhan; Analisis Perbandingan Hukum Pidana Islam dan Positif - Andril Muharram; Abdul Wahid Haddade; Andi Fadli Natsif (Universitas Islam Negeri Alauddin Makassar, 2021)
The problem raised or the purpose of this research is to find out how the concept of legal responsibility for children who commit the crime of murder with a correlation between Islamic law and positive law.To study and answer the problems in this thesis, a multisciplinary approach is used, namely the juridical normative (syar`i) / statutory (statue approach), historical (sociological approach), psychology (psychological approach) approach. This research is classified as a library research, data is collected by analyzing it by using content analysis with relevance to the issues that can be resolved and concluded. After conducting a study of the conspiracy, the results of the research show that children who are criminals can be accounted for legally and in positive law they are given sanctions whose main character and purpose is guidance. There are several laws that regulate this matter, namely Law Number 23 of 2002 concerning child protection. In contrast to Islamic law (fiqh), children's perceptions, and forms of responsibility make child crimes not subject to Uqubah (punishment), takzir (warning) and ta`dabiyyah (guidance) alone, the correlation between the two is the principle of determining punishment for a child as a perpetrator With a positive law that is different from child offenders in the provision of takzir and in terms of ta`dibiyah to children who commit criminal acts, it is maslaha hajiyat (secondary). For this reason, this research is expected to be a material for theoretical comparisons between positive law and Islamic law, comparative material and a reference for further research both relevant and from different variants, and / or reference material for material testing of existing child criminal actsSetelah mengadakan kajian terhadap perseolan tersebut hasil penelitian menuunjukan bahwa bagi anak pelaku pidana dapat dipertanggungjwabakan secara hukum serta dalam hukum positif diberikan sanksi yang sifat dan tujuan utamanya adalah pembinaan. Ada beberapa Undang-Undang yang mengatur tetntang hal tersebut yaitu Undang-Undang Nomor 23 Tahun 2002 tentang perlindungan anak. Berbeda dengan hukum islam (fikih), ersepsi anak, dan bentuk pertanggungjwaban membuat tindak pidana anak tidak dikenakan Uqubah (hukuman), takzir (peringatan) dan ta`dabiyyah (pembinaan) saja, korelasi dari keduanya adalah Asas penetapan hukuman bagi seorang anak sebagai pelaku dengan hukum positif yang berbeda dengan pelaku tindak pidana anak dalam pemberian takzir maupun ditinjau ta`dibiyah kepada anak yang melakukan tindak pidana merupakan maslaha hajiyat (sekunder). untuk itu, penelitian ini diharapkan sebagai bahan perbandingan teoritis antara hukum positif dan hukum islam, bahan perbandingan dan acuan terhadap penelitian selanjutnya baik yang relevan, maupun dari varian yang berbeda, dan atau bahan acuan uji materil terhadap Undang-Undang tindak pidana anak yang telah ada.